Involvement of Hepcidin in Cognitive Damage Induced by Chronic Intermittent Hypoxia in Mice. (4th August 2021) - Zhao, Ya-Shuo; Tan, Miao; Song, Ji-Xian; An, Ji-Ren; Yang, Xin-Yue; Li, Wen-Ya; Guo, Ya-Jing; Ji, En-Sheng
Abstract : Obstructive sleep apnea (OSA) patients exhibit different degrees of cognitive impairment, which is related to the activation of reactive oxygen species (ROS) production by chronic intermittent hypoxia (CIH) and the deposition of iron in the brain. As a central regulator of iron homeostasis, whether hepcidin is involved in OSA-induced cognitive impairment has not been clarified. In order to simulate OSA, we established the mouse model by reducing the percentage of inspired O2 (FiO2 ) from 21% to 5%, 20 times/h for 8 h/day. We found hepcidin was rising during CIH, along with increasing iron levels and neuron loss. Then, we constructed a mouse with astrocyte-specific knockdown hepcidin gene (sh Hamp ). During CIH exposure, the sh Hamp mice showed a lower level of total iron and neuronal iron in the hippocampus, via stabilizing ferroportin 1 (FPN1) and decreasing L-ferritin (FTL) levels, when compared with wild-type (WT) mice. Furthermore, the sh Hamp mice showed a decrease of ROS by downregulating the elevated NADPH oxidase (NOX2) and 4-hydroxynonenal (4-HNE) levels mediated by CIH. In addition, the sh Hamp mice presented improved cognitive deficit by improving synaptic plasticity and BDNF expression in the hippocampus when subjected to CIH. Therefore, our data revealed that highly expressed hepcidin might promote the degradation of FPN1, resulting in neuronal iron deposition, oxidative stress damage, reduced synaptic plasticity, and impaired cognitive performance during CIH exposure.